A relação entre estresse parental e o processo de escolarização em famílias de crianças com Síndrome de Down - ROCHA, Danielle Souza da Paixão (2021)
This Course Conclusion Work (TCC) aims to understand the relationship between parental stress and schooling in families of children with Down Syndrome (DS), comprising two studies in the form of a scientific article. The first study deals with issues related to parental stress and was developed from a literature review, aiming to understand the main focuses of parental stress in caregivers of children with DS and to identify the main caregivers of these children. An exploratory research with a qualitative approach was carried out, using five empirical articles published as of 2006 as a theoretical framework. The result showed that parental stress is related to three important factors - disability, child development and the role of the caregiver . Among the main focuses are the impact of the diagnosis, fear of discrimination and prejudice, the child's lack of autonomy, the caregiver's emotional burden, concern with sexuality, fathers with low levels of education, mothers who cannot work and older children. The articles used for the survey identified mothers as the main caregiver. The second research aimed to understand how maternal perception can interfere in the schooling process of a child with Down Syndrome, taking into account the occurrence of parental stress. This was a descriptive case study with a qualitative approach carried out with a mother of a school-aged girl with DS, in city ​​of Altamira-Pará-Brasil. In the case studied, the results showed that the mother had a positive perception in the context of the birth of a daughter with DS, as well as in her school initiation process, fundamentally by showing low characteristics relevant to parental stress, typical in most families of children with disabilities. It is concluded that the level of parental stress can have a positive or negative relationship in the schooling process of children with DS. Thus, it is possible to state that lower levels of stress experienced by families facilitate the schooling process of children with DS, mainly because less stressed parents have greater belief in the development potential of these children and encourage their attendance at school.